Відповідальність учасників господарських товариств за законодавством України та деяких зарубіжних країн - Бурносенкова, Ірина Артурівна; Бурносенкова, Ирина Артуровна; Burnosenkova, Iryna A. (My University, 2021)
Дисертація на здобуття наукового ступеня кандидата юридичних наук за спеціальністю 12.00.03 – цивільне право і цивільний процес; сімейне право; міжнародне приватне право. – Національний університет «Одеська юридична академія», Одеса, 2021. Дисертація є одним із перших у вітчизняній науці цивільного права спеціальним комплексним порівняльно-правовим дослідженням відповідальності учасників господарських товариств за законодавством України та деяких зарубіжних країн. У дисертації розглянуто правовий статус учасників господарських товариств як суб’єктів цивільно-правової та корпоративної відповідальності. Визначено підстави та умови цивільно-правової відповідальності учасників господарських товариств. Сформульоване поняття та з’ясовано ознаки і підстави корпоративної відповідальності учасників господарських товариств. Проаналізовано зарубіжний досвід правового регулювання відповідальності учасників господарських товариств. Визначено основні напрями вдосконалення законодавства України про відповідальність учасників господарських товариств з урахуванням позитивного законодавчого досвіду зарубіжних країн. Сформульовано конкретні науково-обґрунтовані пропозиції щодо вдосконалення актів чинного законодавства України в частині правової регламентації відповідальності учасників господарських товариств.

Диссертация на соискание научной степени кандидата юридических наук по специальности 12.00.03 – гражданское право и гражданский процесс; семейное право; международное частное право. – Национальный университет «Одесская юридическая академия», Одесса, 2021. Диссертация является одним из первых в отечественной науке гражданского права специальным комплексным сравнительно-правовым исследованием ответственности участников хозяйственных обществ по законодательству Украины и некоторых зарубежных стран. В диссертации рассмотрен правовой статус участников хозяйственных обществ как субъектов гражданско-правовой и корпоративной ответственности. Определены основания и условия гражданско-правовой ответственности участников хозяйственных обществ. Сформулировано понятие и выяснены признаки и основания корпоративной ответственности участников хозяйственных обществ. Проанализирован зарубежный опыт правового регулирования ответственности участников хозяйственных обществ. Определены основные направления усовершенствования законодательства Украины об ответственности участников хозяйственных обществ с учетом положительного законодательного опыта зарубежных стран. Сформулированы конкретные научно-обоснованные предложения по совершенствованию актов действующего законодательства Украины в части правовой регламентации ответственности участников хозяйственных общест

Dissertation for the Candidate of Legal Sciences Degree in the Specialty 12.00.03 – Civil Law and Civil Procedure; Family Law; Private International Law. – National University “Odessa Law Academy”, Odessa, 2021. Dissertation is one of the first special comprehensive comparative legal studies in domestic science of Civil Law of the liability of participants of business entities under the legislation of Ukraine and particular foreign countries. Peculiarities of legal regulation of the status of different types of business entities, which acts as a generic concept, were analyzed: joint stock companies, limited liability companies, additional liability companies, full liability companies and differentiated liability companies, their main features were identified. An updated definition of civil liability of participants of business entities is proposed as the application of property sanctions to the offender by the authorized (jurisdictional) body or creditor in order to compensate for property and / or moral damage caused by the offender to the victim. The bases and conditions of civil liability of participants of business entities were defined and characterized. The definition and grounds of corporate responsibility of participants of business entities were formulated and clarified. Corporate liability is a sanction that is applied within the framework of corporate legal relations and is a negative (adverse) additional consequence of property, moral or organizational nature for violation of corporate rights, abuse of such rights, violation of legally protected interests and failure to perform (improper performance) of the duties, provided by the legislation, corporate agreement, charter, local legal acts. Corporate liability of participants of business entities has following features: it is a sanction; entails for the violator additional negative consequences of property, organizational, moral nature; is based on a corporate or managerial offense; applies to participants of business entities and corporate entities. The foreign experience of legal regulation of liability of participants of business entities (the UK, USA, Germany, Austria, etc.) was analyzed. The main directions of improvement of the legislation of Ukraine regarding the liability of participants of business entities were determined, taking into account positive legislative experience of foreign countries. Specific scientifically substantiated proposals on improvement of acts of the current legislation of Ukraine in the part of legal regulation of liability of participants of business entities were formulated.
дис. ... канд. юрид. наук: 12.00.03
Бурносенкова І.А. Відповідальність учасників господарських товариств за законодавством України та деяких зарубіжних країн: дис. ... канд. юрид. наук: 12.00.03 / Бурносенкова Ірина Артурівна. Одеса, 2021. 203 с.
Keywords: законодавство деяких зарубіжних країн; законодавство України; корпоративна відповідальність; цивільно-правова відповідальність; учасники господарських товариств; господарські товариства; юридичні особи; законодательство некоторых зарубежных стран; законодательство Украины; корпоративная ответственность; гражданско-правовая ответственность; участники хозяйственных обществ; хозяйственные общества; юридические лица; legislation of particular foreign countries; legislation of Ukraine; corporate liability; civil liability; members of business entities; business entities; legal persons